2017
DOI: 10.14739/2310-1210.2017.5.110099
|View full text |Cite
|
Sign up to set email alerts
|

The impact of concomitant syndrome of somatopsychic dysfunction on the quality of patients with chronic obstructive pulmonary disease life

Abstract: Вплив супутнього синдрому соматопсихічної дисфункції на якість життя хворих із хронічним обструктивним захворюванням легень А. О. Довгань, Т. В. Константинович, Ю. М. Мостовой, О. В. Довгань, Д. В. ДіденкоВінницький національний медичний університет імені М. І. Пирогова, УкраїнаМета роботи -оцінити параметри якості життя (ЯЖ) у хворих на хронічне обструктивне захворювання легень (ХОЗЛ) залежно від виду та виразності супутнього клінічно значущого інтегративного синдрому соматопсихічної дисфункції (СПД).Матеріал… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The impact of COPD on QOL is closely linked to the onset of anxiety and depression [4]. t is known that clinical presentation and prognosis of the disease are negatively affected by disorders of psychological status that develop with COPD [1]. Contemporary scientists found that the neuro-vegetative and acquired psychological disorders are significant components of the pathogenetic complex, which determine development, course and prognosis of COPD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of COPD on QOL is closely linked to the onset of anxiety and depression [4]. t is known that clinical presentation and prognosis of the disease are negatively affected by disorders of psychological status that develop with COPD [1]. Contemporary scientists found that the neuro-vegetative and acquired psychological disorders are significant components of the pathogenetic complex, which determine development, course and prognosis of COPD.…”
mentioning
confidence: 99%
“…Contemporary scientists found that the neuro-vegetative and acquired psychological disorders are significant components of the pathogenetic complex, which determine development, course and prognosis of COPD. Therefore, it seems logical that treating patients with COPD should have an integrated approach, and include not only the treatment of the underlying disease, but mandatory correction of associated disorders, including the psychoemotional sphere [1].…”
mentioning
confidence: 99%